Beyond Adoption Metrics: A Multi-Criteria Performance Assessment of QRIS in Advancing MSME Digitalization - Muhammad Zabir Zainuddin (ARRUS Journal of Social Sciences and Humanities, 2026)
The Quick Response Code Indonesian Standard (QRIS) has significantly accelerated the rapid development of electronic payment systems in Indonesia, accelerating the country's transition to a cashless economy. However, the majority of recent evaluations have focused on measuring adoption rates and transaction volumes, thereby ignoring the complex effects of QRIS on small business operations. By developing a quantitative framework for Multi-Criteria Decision Analysis (MCDA) that goes beyond simple descriptive analysis in assessing the contributions of QRIS, this study aims to close the research gap. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and the Analytic Hierarchy Process (AHP), whose criteria weights were determined using the Geometric Mean Method, were both used in an applied quantitative technique to rank MSME performance. This analysis analyzed six criteria: financial transparency, consumer trust and digital literacy, cost reduction, revenue growth, transactional efficiency, and formal financing. The findings indicate that revenue growth and formal funding were identified as the most significant criteria, each with a weight of 0.20, and that the results derived from the AHP had an adequate consistency level (CR = 0.067). With the top performance achieving a closeness coefficient of 1.000, the TOPSIS technique ranks the five MSMEs as follows: A5 > A3 > A4 > A1 > A2. By shifting the emphasis from access to measurable performance outcomes, the findings promote financial inclusion theory and support digital payment ecosystem theory by highlighting the importance of organizational capability in attaining fintech advantages. Policy implications suggest that targeted MSME capacity-building and credit-linkage integration should be implemented in tandem with the expansion of QRIS. Overall, the study demonstrates that performance-based MCDA evaluation offers a strict foundation for regulating digital payments in emerging economies.